Porphyria Cutanea Tarda and HFE Gene Mutations in Argentina - Colombo, Federico Pablo (2014)
Aims: Porphyria Cutanea Tarda (PCT), the most common of porphyrias is triggered by several factors, including iron overload. Type I Hereditary Hemochromatosis is inherited as an autosomal recessive trait of the mutation p.C282Y or as a compound heterozygous form p.C282Y/p.H63D in HFE gene. Our aim was to study the frequency of HFE mutations in Argentinean PCT patients and in control subjects. Place and Duration of Study: CIPYP, CONICET, Hospital de Clínicas José de San Martín: Av. Córdoba 2351, 1º subsuelo, Buenos Aires, Argentina (1120). Between March 2008 and March 2010. Methodology: We analyzed HFE mutations in 103 PCT patients (67 males, 36 females) and in 93 control subjects (63 males and 30 females). PCT patients were classified as familial, sporadic or Type III PCT measuring URO-D activity in red blood cells. HFE mutations were detected by amplification and automatic sequencing of exons 2 and 4 in the HFE gene. In some cases p.H63D and p.C282Y mutations were also detected by digestion with restriction enzymes (Mbo I for p.H63D and Rsa I for p.C282Y), followed by 3% polyacrilamide gel electrophoresis. Results: In PCT group, 34.9% carried mutation p.H63D (26.2% heterozygous, 5.8% homozygous and 2.9% as p.C282Y/p.H63D) and 7.8% carried mutation p.C282Y (2.9% in heterozygocity, 1.9% in homozygocity and 2.9% as p.C282Y/p.H63D). In the control group, 30.1% carried p.H63D (28% in heterozygous and 2.1% in homozygous), and 5.4% had p.C282Y in heterozygosity. There were no significant differences between sporadic and familial PCT and neither between PCT and control groups. Our findings are in agreement with the prevalence of the Mediterranean origin of our patients, where p.C282Y mutation is less common than p.H63D mutation. Conclusion: We conclude that mutations in HFE gene do not play a relevant role in the triggering of PCT in our country. - See more at: http://www.sciencedomain.org/abstract.php?iid=380&id=12&aid=2851#.UtbUqtLuKos